Lari Berbeban 1 Kg pada Kaki 100 M 4 Repetisi Meningkatkan Kecepatan Tendangan Mawashi Geri Dojo SMP St. Theresia - Lukas D Bili; Dixon E.M. Taek Bete (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
The purpose of this study was to determine running training with a load of 1 kg at 100 m 4 legs. Repetitions Increase Mawashi Geri's Kicking Speed ​​at Dojo Karateka SMP St. Theresia-Kupang City. This research method is an experimental method with the design research design is one group pre-test and post-test design. This research was conducted on Karate members at the Dojo SMP St. Theresia-Kota Kupang. The time used in implementing the training program is 6 weeks. The population in this study were Karate athletes. Sampling using random sampling technique (lottery), so that the sample used amounted to 10 people. Data collection techniques using action tests and documentation. Data analysis using the t-test formula. The results of data analysis showed that the mean of the initial test = 32.9, the mean of the final test = 42.9 and the result of the t-count = 43.455. The calculation result is then compared to df = N-1 (10-1) = 9. Then it is obtained 1,833 at the 5% significance level. It means that t-count (43.455)> t-table (1.833), which means that the alternative hypothesis / Ha is "accepted" while the null hypothesis / Ho is "rejected", because the value of t-count> t-table. Running training with a load of 1 kg on the leg 100 m 4 reps can increase the kick speed of mawashi geri karate athletes Keywords: Running, Speed, Mawashi Geri's Kick